Stay on target? - Galster, Jason A. (Audiology Today)
The focus on gain and targets has obscured the most important part of the real-ear measurement-audibility. The topic of audibility is familiar; after all, a primary goal of fitting hearing aids is restoring the audibility of average speech. Yet audibility is not a commonly observed metric in many clinics today.